HARMFULNESS OF MYCOSISS ON CULTURE OF GARLIC WINTER-ANNUAL IN THE CONDITIONS OF MOSCOW REGION - T. M. Seredin; L. I. Gerasimova; E. G. Kozar; I. A. Engalycheva; E. V. Baranova (Овощи России, 2018)
One of stressful factors the reducing harvest and quality of bulbs of garlic winter (Allium sativum L.) defeat is diseases of various etiology. Studying of influence of factors of the external environment and stability of a genotype on prevalence of diseases on landings of garlic winter and degree of their injuriousness in the conditions of the Moscow region was the purpose of researches; assessment of collection and selection samples of garlic winter and identification among them steady against the most economically significant diseases. Object of researches were grades and collection samples of garlic of the Federal Scientific Vegetable Center, winter from collections, and other selection institutions. Field experiments and assessment were carried out on a natural infectious background for a number of years. It is as a result established that in the conditions of the Moscow region during vegetation of a plant of garlic winter mainly are surprised mushroom diseases (mycoses) among which the dominating position is taken by fusariosis (micromycetes of the sort Fusarium spp). Defeat of garlic fusariosis is shown annually and with different intensity, depending on weather conditions. The analysis of literature and results of our researches show that number and a ratio of types of Fusarium spp. in a pathogenic complex changes in last years. The types which are earlier not noted on the culture of garlic in the Moscow region (since 2009 – F. avenacium, F. proliferatum, F. subglutinans and F. semitectum are registered; since 2017 – F. gibbosum and F. nivale). In a complex with highly aggressive types of F. solani and F. oxysporum they enhance injuriousness of fuzariosis withering and rots. Mushrooms of the sort Alternaria and other micromycetes of the sorts Stemfillium, Pythium, Embilisia, Verticillum, Cladosporium in the conditions of the Moscow region meet mainly in a complex Fusarium. Gray rot (the activator – Botrytis allii L.) it is more often shown in storage time and transportations of bulbs of garlic. These micromycetes enhance injuriousness of fusariosis and increase losses of a harvest of garlic winter, especially, in the conditions of sharp fluctuations of average daily temperatures and humidity of the soil during the different periods of vegetation. Results of long-term assessment are given in article, grades and perspective collection samples of garlic winter the steadiest against defeat with diseases in the conditions of the changing climate of a zone of Non-Black Earth Region are allocated.